Analysis of Clean Water Quality in Kolongan Village, Talawaan District - Tarigan, Irama Rauli Tarigan; Rampengan, Mercy; Ogi, Nova L I M (Indonesian Biodiversity Journal, 2024)
Kolongan Village is one of the villages in Talawaan district of North Minahasa, North Sulawesi. In the village of Kolongan, some springs are potentially a clean water source for the people of the village. This research aims to analyze the quality of the springs in the village of Kolongan Talawaan, Prefectures as a water source. This type of research is quantitative, and the method used in this research is the Indonesian National Standard (SNI) according to the water quality parameters that have been established with the direct observation plan of the physical properties of water and with the laboratory testing plan for the observation of water chemical and biological properties with indicators of iron, sensitivity, manganese, E.coli, taste, and smell. The research was conducted from July 24, 2021, to September 20, 2021. The water quality measurement results in the spring in one village of Kolongan showed iron <0.0086 mg/L, iron 69-93 mg/ L, manganese 0.03-0.07 mg / L, E. coli, 11 CFU, not sensitive and odorless. Water source 2 showed iron <0.086 mg / l, density 75-85 mg/ l, manganese 0.02-0.03 mg/l, and E. coli, 3.6-9.2 CFU, is not sensible and odorless. The pollution index calculation indicates that the springs in Kolongan Village belong well. However, because they still contain biological reservoirs, it is necessary to have an advanced process for them to be consumed by the community.